2014
DOI: 10.1016/j.jcp.2014.01.036
|View full text |Cite
|
Sign up to set email alerts
|

A spectral-Lagrangian Boltzmann solver for a multi-energy level gas

Abstract: In this paper a spectral-Lagrangian method is proposed for the full, non-linear Boltzmann equation for a multi-energy level gas typical of a hypersonic re-entry flow. Internal energy levels are treated as separate species and inelastic collisions (leading to internal energy excitation and relaxation) are accounted for. The formulation developed can also be used for the case of a gas mixture made of monatomic gases without internal energy (where only elastic collisions occur). The advantage of the spectral-Lagr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Tcheremissine & Agarwal (2008) solved the WCU equation for normal shock waves in nitrogen, and found that the computational cost is larger by about two orders of magnitude than for a monatomic gas. Recently, a spectral-Lagrangian method with computational memory and cost of the order of N 4 e N 6 v has been proposed (Munafò et al 2014), where N e is the number of discrete internal energy levels; for N e = 5 and N v = 16, the memory needed is approximately 88 GB, while the time needed for calculating the collision operators once is approximately 3 s using 12 compute threads, which restricts its suitability when applied to real problems. The direct simulation Monte Carlo (DSMC) method proposed by Bird (1994), using the Larsen-Borgnakke collision rule (Borgnakke & Larsen 1975) for the translationalinternal energy exchange, is a good alternative because of its linear computational cost with the number of simulated particles and far smaller memory requirements.…”
mentioning
confidence: 99%
“…Tcheremissine & Agarwal (2008) solved the WCU equation for normal shock waves in nitrogen, and found that the computational cost is larger by about two orders of magnitude than for a monatomic gas. Recently, a spectral-Lagrangian method with computational memory and cost of the order of N 4 e N 6 v has been proposed (Munafò et al 2014), where N e is the number of discrete internal energy levels; for N e = 5 and N v = 16, the memory needed is approximately 88 GB, while the time needed for calculating the collision operators once is approximately 3 s using 12 compute threads, which restricts its suitability when applied to real problems. The direct simulation Monte Carlo (DSMC) method proposed by Bird (1994), using the Larsen-Borgnakke collision rule (Borgnakke & Larsen 1975) for the translationalinternal energy exchange, is a good alternative because of its linear computational cost with the number of simulated particles and far smaller memory requirements.…”
mentioning
confidence: 99%
“…The method employs Fourier-Galerkin discretization in velocity space, and handles binary collisions in the corresponding frequency space. The method has spectral accuracy, and can deal with mixtures with large molecular mass ratios at a computational cost of O( p m r M 2 N 4 log N ), which is much smaller than the conventional spectral method's cost of O(m 3 r N 6 ) [57]. Numerical results have been presented for the spatially-homogeneous relaxation of pseudo-Maxwell molecules, and for spatially-inhomogeneous problems (such as normal shock waves, planar Fourier/Couette flows, and a two-dimensional temperature-driven flow) involving hardsphere gases with molecular mass ratios up to 36.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the procedure in deriving this FSM for monatomic gas mixtures is similar to that for a single-species Boltzmann collision operator [35], so it can be proved that the FSM presented here conserves mass, while the errors in achieving momentum and energy conservation are spectrally small. These errors, however, can be removed using the method of Lagrangian multipliers [37,57].…”
Section: Fast Spectral Methods For the Cross-collision Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that we can obtain the symmetry relations (35), possibly after a scaling (34). Actually assuming a convenient reciprocity relation [26], this will be the case.…”
Section: Multicomponent Mixturesmentioning
confidence: 99%